2019
DOI: 10.3390/en12020327
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effects of CO2 Displacement Methods on Petrophysical Property Changes of Ultra-Low Permeability Sandstone Reservoirs Near Injection Wells

Abstract: The petrophysical properties of ultra-low permeability sandstone reservoirs near the injection wells change significantly after CO2 injection for enhanced oil recovery (EOR) and CO2 storage, and different CO2 displacement methods have different effects on these changes. In order to provide the basis for selecting a reasonable displacement method to reduce the damage to these high water cut reservoirs near the injection wells during CO2 injection, CO2-formation water alternate (CO2-WAG) flooding and CO2 floodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…However, Drexler et al (2019) noted a reduction in weight, porosity, pore volume and permeability of the sample after injecting carbonated water (desulphated seawater saturated with CO2), while Abbaszadeh et al (2016) reported a reduction in porosity and the sample's weight, but an increase in the permeability. By contrast, Wang et al (2019) observed almost no changes in the porosity but a significantly lower permeability. Most studies noted the importance of rock dissolution as such, and the transport and deposition of fine particles (e.g., Jia, 2019;Mahzari et al, 2019).…”
Section: Introductionmentioning
confidence: 71%
“…However, Drexler et al (2019) noted a reduction in weight, porosity, pore volume and permeability of the sample after injecting carbonated water (desulphated seawater saturated with CO2), while Abbaszadeh et al (2016) reported a reduction in porosity and the sample's weight, but an increase in the permeability. By contrast, Wang et al (2019) observed almost no changes in the porosity but a significantly lower permeability. Most studies noted the importance of rock dissolution as such, and the transport and deposition of fine particles (e.g., Jia, 2019;Mahzari et al, 2019).…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, CO2-brine-rock interactions lead to dissolution of carbonate minerals and destruction of clay mineral structure in rocks. Metal carbonate precipitation occurs due to changes in pH and the concentration of metal ions (i.e., Ca 2+ , Mg 2+ , Fe 2+ ) in the fluid of the cores (Equations 1-3), and additional clay particles are released caused by structural instability [29][30] . It has been reported that low-permeability sandstones undergo CO2 flooding and CO2-WAG flooding, and the concentration of suspended solid particles in the produced brine ranges from 0 to 6720 mg/L with an average size of 1049.7 nm [24] .Three of the most common carbonate minerals formed in pores and capable of blocking pore throats are given by the equations CO2 + H2O + CaCO3⇌ Ca(HCO3)2,…”
Section: Permeability Damagementioning
confidence: 99%
“…Foam has different applications in oil and gas industry such as in drilling, hydraulic fracturing, and in enhanced oil recovery (EOR) [2][3][4][5][6]. CO 2 flooding is one of the most commonly used EOR method that involves the injection of compressed CO 2 [7][8][9]. In EOR methods that employ low viscous fluids as displacing slugs such as CO 2 flooding, the foam is applied to improve the sweep efficiency by controlling the gas mobility.…”
Section: Introductionmentioning
confidence: 99%